Academic Engagement with Wadden Sea Stakeholders: A Review of Past Foci and Possible Futures - Gadsden, Gabriel I.; Peters, Kimberley; Dajka, Jan-Claas (Frontiers in Marine Science, 2022)
The Wadden Sea became a UNESCO World Heritage Site in 2009 owing to its geographical and ecological importance. Given its status and its global recognition, academic understanding of, and engagement with, a diverse set of stakeholders is crucial to the sustainability of the Wadden Sea and the wildlife that inhabit its transnational boundaries. As such, this paper reviews with whom, how, and to what extent the academy has engaged with Wadden Sea stakeholders. This study finds that stakeholder groups (whom, with vested interests in the sea, might be expected to be present) are missing from academic publications focused on stakeholders in the Wadden Sea. Moreover, existing studies tend to focus on singular, categorized stakeholder ‘groups’, and lack transboundary integration, as well as reference to UN Sustainability Goal 14 – a key target for environmental protection. In sum, the review provides (1) an analysis of academic work that engages Wadden Sea stakeholders to assist future researchers undertaking work in this global ecologically significant area, and (2) a discussion of where future academic work might be developed.